Differential Phagocytic Properties of CD45low Microglia and CD45high Brain Mononuclear Phagocytes—Activation and Age-Related Effects - Rangaraju, Srikant; Raza, Syed Ali; Li, Noel Xiang’An; Betarbet, Ranjita; Dammer, Eric B.; Duong, Duc; Lah, James J.; Seyfried, Nicholas T.; Levey, Allan I. (Frontiers in Immunology, 2018)
In the central nervous system (CNS), microglia are innate immune mononuclear phagocytes (CNS MPs) that can phagocytose infectious particles, apoptotic cells, neurons and pathological protein aggregates such as Aβ in Alzheimer’s disease (AD). While CD11b+CD45low microglia account for the majority of CNS MPs, a small population of CD11b+CD45high CNS MPs is also recognized in AD that surround Aβ plaques. These transcriptionally-distinct and pathologically-relevant CD45high cells have unclear origin and undefined phagocytic characteristics. We have comprehensively validated rapid flow cytometric assays of bulk-phase and amyloid β fibril (fAβ) phagocytosis and applied these to study acutely isolated CNS MPs. Using these methods, we provide novel insights into differential abilities of CD11b+ CD45low and CD45high CNS MPs to phagocytose macroparticles and fAβ under normal, acute and chronic neuroinflammatory states. CD45high CNS MPs also highly upregulate TREM2, CD11c and several disease-associated-microglia (DAM) signature genes, and have a higher phagocytic capacity for Aβ as compared to CD45low microglia in the 5xFAD mouse model of AD that becomes more apparent with ageing. Our data suggest an overall pro-phagocytic and protective role for CD11b+CD45high CNS MPs in neurodegeneration, which if promoted, could be beneficial.